Modelling and analysis of a hybrid solar concentrating-waste incineration power plant. (10th April 2019) - Sadi, M.; Arabkoohsar, A.
Abstract: Concentrating solar power plant will be a key component of the future energy systems in which the share of renewable energy is extremely high. A major challenge of this technology is, however, its intermittent power output, slowing down its rate of implementation in the global energy matrix. As such, waste incineration is a popular technology in the developed countries as a smart measure for the disposal of municipal waste and generating free energy. In this study, a hybrid configuration of a concentrating solar power plant accompanied with a waste incineration unit is proposed. In the proposed system, the waste incinerator offers a variable heating duty in order to regulate the power output of the concentrating solar power plant. The hybrid plant is designed for a case study in Denmark and is thermodynamically analyzed. The results of the simulations are presented and discussed. It is shown that the hybrid system can pave the bed for increasing the share of solar thermal power and bringing more waste incinerators to the electricity market. A 10 MWe hybrid power plant may prevent up to 8000 tonnes of carbon dioxide equivalent emission per month. The overall efficiency of the hybrid system is expected to be 24%. Highlights: A hybrid concentrating solar power plant accompanied with a waste incineration unit is proposed. The proposed system provides a cost-effective and dispatchable electricity to the grid. Thermodynamic performance and environmental impacts of the system are investigated. The net annual energy efficiency of the system is approximately 24%. The system contributes to the prevention of a large amount of CO2 e emission.